HOME VISITING IN THE FAMILY HEALTH STRATEGY: ITS PERCEPTION AMONG NURSES - Edirlei Machado dos Santos; Sandra Helena Gomes Morais (Universidade Federal do Paraná, 2011)
Currently, home visiting is an essential instrument for the practice of primary health actions, especially lined with the Family Health Strategy. This descriptive and exploratory study with a qualitative approach aims to identify and analyze how nurses perceive home visiting. Thematic analysis was used to analyse the data. Two thematic unities were identified: the home visit as a possibility for creating links and the home visit as a possibility for integral assistance. Thus, the home visit as an instrument for health work processes - in particular in primary health attention - is a facilitating element for public health service users and also an integral way of attending them, in which the real needs of individuals and families can be identified.